Monnaie frappée et pensée abstraite dans la Grèce du viie siècle avant J.-C. - Bernard Ancori (Recherches Germaniques)
This article proposes a critical reading of Alfred Sohn-Rethel’s thesis, which claims that money, appearing in ancient Greece around 680 BC, was the original cause of conceptual thought. It will argue instead that the almost simultaneous emergence of monetary exchange and conceptual thought was a matter of correlation, rather than causation. To show this correlation it will first summarize Sohn-Rethel’s central argument, and then describe the process leading–in around 630 BC, rather than 680 BC–to the emergence of conceptual thought and monetary exchange. Finally, it will show that the same type of process led to the resurgence of these two phenomena at the turn of the 12th-13th centuries in the Medieval West, and propose an interpretation in terms of the evolution of the system of Indo-European ideology.